"In You All Things”: Biblical Influences on Story, Gameplay, and Aesthetics in Guerrilla Games’ Horizon Zero Dawn - Dyer, Rebekah (Journal for interdisciplinary biblical studies (JIBS), 2021)
This article considers several instances of biblical reception in the science-fiction role-playing game Horizon Zero Dawn (Guerrilla Games/Sony, 2017). The game’s characterisation of technology, science, and religion has led some commentators to understand Horizon Zero Dawn as presenting a firm rejection of religious narratives in favour of scientific perspectives. However, closer examination of the game’s biblical influences reveals that Horizon Zero Dawn employs religious ideas of the past and present to articulate its vision of a post apocalyptic future. The integration of biblical material into the story, aesthetics, and gameplay of Horizon Zero Dawn provides multi-layered interactions with specific characters, images, and ideas from the Bible. The game engages with the narrative of David and Goliath, the plague imagery of the Exodus narrative, and New Testament apocalyptic imagery in order to tell a story of ecological collapse, global apocalypse, and technological re- creation. Investigation of its biblical influences demonstrates that Horizon Zero Dawn embraces religious narratives insofar as they may be integrated into the game’s discussion of human responsibility, environmental sustainability, and the existential concerns of its post-apocalyptic scenario.